Negotiating Gender Justice in Islamic Religious Education: A Critical-Appreciative Study of Curriculum, Epistemology, and Pedagogical Discourse - Iffah Khoiriyatul Muyassaroh (Eshraq: Journal of Islamic Studies, 2025)
This study investigates the entrenchment of gender bias within the epistemological and curricular framework of Islamic Religious Education (IRE) in Indonesia. Utilizing a qualitative-conceptual method rooted in critical discourse analysis and maqasidi hermeneutics, the research reveals how patriarchal norms are embedded in textbooks, pedagogical practices, and interpretive traditions. Rather than opposing tradition, this study proposes a critical-appreciative framework that integrates Islamic ethical values such as justice (‘adl), compassion (rahmah), and trust (amanah) with transformative pedagogies. The findings indicate that literalist and androcentric tendencies in IRE curricula reinforce male-dominated religious authority and marginalize female voices. Through the negotiation of maqasid and contemporary social contexts, the study advocates for inclusive reform that reclaims women’s epistemic agency without resorting to ideological feminism. Pedagogical recommendations include reconfiguring curriculum content, empowering teachers with contextual hermeneutics, and institutionalizing reflective, dialogical learning models. Ultimately, this article contributes to envisioning an IRE curriculum that is both faithful to Islamic tradition and responsive to the ethical imperatives of gender justice